Peary's discovery of the North Pole - Moore, J. Hampton (Joseph Hampton), 1864-1950. (Washington : [s.n.], 1910)
"Speech of Hon. J. Hampton Moore of Pennsylvania in the House of Representatives, March 22, 1910." Mode of access: Internet.